Massive Osteolytic Lesion of the Femur after Total Knee Arthroplasty - Cardoso, Afonso (Arthroplast Today, 2020)
Various failure mechanisms have been identified in total knee arthroplasty (TKA). We hereby present one case of failure, which stands out because of its rapid and destructive progression. We report the case of a 72-year-old Caucasian female patient who developed a large bone osteolytic lesion of the femur after TKA. The patient presented to our hospital 7 years after the initial surgery, complaining of persistent knee pain. The lesion affected the distal half of the femur and, after a diagnostic workup, required a resection of 20 cm and reconstruction with a tumor prosthesis. Subsequent pathological analysis revealed a reaction to cement and prosthesis components. Periprosthetic osteolysis continues to be a major problem, and a reaction to cement and prosthesis components can be an elusive cause of TKA failure.